User Generated Content dan Pemanfaatan Media Sosial Dalam Perkembangan Industri Pariwisata: Literature Review - Herman Purba; Irwansyah Irwansyah (Professional: Jurnal Komunikasi dan Administrasi Publik, 2022)
The development of social media today can be used to maximize every potential of the tourism industry in the community. User Generated Content (UGC) is one of the strengths of social media because users can produce their own content and attract other consumers. UGC has an important role to create creation and interaction in the form of digital content, helping tourists to express, interact and collect or disseminate information as part of tourism communication. The method used in this research is literature review. The results of this study show that UGC is also a positive breakthrough and has a significant influence in building a destination image to influence the loyalty of a tourist through the use of social media, interesting visual content, and supported by persuasive captions by involving the audience to get involved in it.